Answer:
-1
Explanation:
We are given that a function
![f(x)=-32(2)^(x-3)+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qq494lkge813adtj1apv1776zdvohw52dg.png)
We have to find the y- intercept of the exponential function.
To find the y- intercept of given exponential we will substitute x=0
Substitute x=0 then, we get
![f(0)=-32(2)^(0-3)+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k0wauxr4irfbpy2f9pfob9cvo6ku8v1v0h.png)
![f(0)=-32(2)^(-3)+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4816j4s78n97utl40ijn9tgxdmr6q030vu.png)
![f(0)=-(32)/((2)^3)+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6mecwgsym7guudkm4814awqxvx8isek54y.png)
By using property
![a^(-x)=(1)/(a^x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/xe28s667iy6nquy4coua4h7qtrgmgn14io.png)
![f(0)=-(32)/(8)+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t2otkp9xu7y531zvxpvahm93j8qqgv59pf.png)
![f(0)=-4+3=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4o0n5l0nd52w4ko23yr6k1krbfmt4gjtj2.png)
Hence, the y- intercept of given exponential =-1